2019
DOI: 10.1101/628602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new role for Notch in the control of polarity and asymmetric cell division of developing T cells

Abstract: A fundamental question in biology is how single cells can reliably produce progeny of different cell types. Notch signalling frequently facilitates fate determination. Asymmetric cell division (ACD) often controls segregation of Notch signalling by imposing unequal inheritance of regulators of Notch. Here, we assessed the functional relationship between Notch and ACD in mouse T cell development. To attain immunological specificity, developing T cells must pass through a pivotal stage termed β-selection,

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(123 reference statements)
1
5
0
Order By: Relevance
“…1, C–E ). As previously found ( Charnley et al, 2019 ; Pham et al, 2015 ), the cytokine receptor CD25 was not polarized ( Fig. 1 C ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…1, C–E ). As previously found ( Charnley et al, 2019 ; Pham et al, 2015 ), the cytokine receptor CD25 was not polarized ( Fig. 1 C ).…”
Section: Resultssupporting
confidence: 88%
“…Our previous observation that the MTOC was recruited to the interface with the stromal cell ( Charnley et al, 2019 ; Pham et al, 2015 ), reminiscent of an immunological synapse in mature cells ( Alcover et al, 2016 ; Dustin and Baldari, 2017 ), led us to assess whether developing T cells might also form an immunological synapse. Flow cytometry confirmed that pre-TCR components, including the pTα chain, TCRβ chain, LCK, LAT, and PKCθ, were expressed in DN3 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Notch has an important role in control of polarity and orientation of the mitotic spindle in several cell types. 25,[137][138][139] Indeed, aberrant Notch activation disrupted cell polarity signaling, leading to a notable number of abnormal mitoses in renal progenitors, through the deregulation of pathways involved in cell cycle checkpoints and/or mitotic spindle control. 25 Hippo pathway.…”
Section: Injury Repairmentioning
confidence: 99%